Effects of dietary addition of zinc and (or) monensin on performance, rumen fermentation and digesta kinetics in beef cattle - Arelovich, H.M.=700 1 Laborde, H.E.; Amela, M.I.; Torrea, M.B.; Martinez, M.F.
(Es, En)
Ilus., 42 ref.
Keywords: GANADO DE CARNE; ADITIVOS; CINC; PRODUCTIVIDAD; DIGESTION RUMINAL; CONSUMO; GANANCIA DE PESO; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH